Malaysians urged to grab chance to work in construction sector - Bernama, . (The Borneo Post Sdn Bhd., 2021)
KUALA LUMPUR: Malaysians must grab the chance to work in the construction sector which is currently facing a significant shortage of workers due to the Covid-19 pandemic, said Senior Minister of Works Datuk Seri Fadillah Yusof.